The design and rationale of a multicenter clinical trial comparing two strategies for control of systolic blood pressure: The Systolic Blood Pressure Intervention Trial (SPRINT). (October 2014) - Ambrosius, Walter T; Sink, Kaycee M; Foy, Capri G; Berlowitz, Dan R; Cheung, Alfred K; Cushman, William C; Fine, Lawrence J; Goff, David C; Johnson, Karen C; Killeen, Anthony A; Lewis, Cora E; Oparil, Suzanne; et al.
Background: High blood pressure is an important public health concern because it is highly prevalent and a risk factor for adverse health outcomes, including coronary heart disease, stroke, decompensated heart failure, chronic kidney disease, and decline in cognitive function. Observational studies show a progressive increase in risk associated with blood pressure above 115/75 mm Hg. Prior research has shown that reducing elevated systolic blood pressure lowers the risk of subsequent clinical complications from cardiovascular disease. However, the optimal systolic blood pressure to reduce blood pressure–related adverse outcomes is unclear, and the benefit of treating to a level of systolic blood pressure well below 140 mm Hg has not been proven in a large, definitive clinical trial. Purpose: To describe the design considerations of the Systolic Blood Pressure Intervention Trial (SPRINT) and the baseline characteristics of trial participants. Methods: The Systolic Blood Pressure Intervention Trial is a multicenter, randomized, controlled trial that compares two strategies for treating systolic blood pressure: one targets the standard target of <140 mm Hg, and the other targets a more intensive target of <120 mm Hg. Enrollment focused on volunteers of age ≥50 years (no upper limit) with an average baseline systolic blood pressure ≥130 mm Hg and evidence of cardiovascular disease, chronic kidney disease, 10-year Framingham cardiovascular disease risk score ≥15%, or age ≥75 years. The Systolic Blood Pressure Intervention Trial recruitment also targeted three pre-specified subgroups: participants with chronic kidney disease (estimated glomerular filtration rate <60 mL/min/1.73 m 2 ), participants with a history of cardiovascular disease, and participants 75 years of age or older. The primary outcome is first the occurrence of a myocardial infarction (MI), acute coronary syndrome, stroke, heart failure, or cardiovascular disease death. Secondary outcomes include all-cause mortality, decline in kidney function or development of end-stage renal disease, incident dementia, decline in cognitive function, and small-vessel cerebral ischemic disease. Results: Between 8 November 2010 and 15 March 2013, Systolic Blood Pressure Intervention Trial recruited and randomized 9361 people at 102 clinics, including 3331 women, 2648 with chronic kidney disease, 1877 with a history of cardiovascular disease, 3962 minorities, and 2636 ≥75 years of age. Limitations: Although the overall recruitment target was met, the numbers recruited in the high-risk subgroups were lower than planned. Conclusions: The Systolic Blood Pressure Intervention Trial will provide important information on the risks and benefits of intensive blood pressure treatment targets in a diverse sample of high-risk participants, including those with prior cardiovascular disease, chronic kidney disease, and those aged ≥75 years.